Unidirectional-link detection algorithms in wireless sensor networks - SANG Jun-jun; SHI Sheng-fei; LI Jiang-zhong; XIONG Shu-guang (Tongxin xuebao)
Three distributed approaches were presented to detect unidrectional-links and to support routing protocols to use them. The main idea of these approaches was using Beacon message to exchange some information between nodes. Real link data based experiments show that these approaches can reduce the average length of routing path by 37.8%~39.24%, and can improve the average deliver ratio by 23.82%. Simulation experiments show that these ap- proaches are both efficient and scalable.